Implementasi Bangunan Ekonomi Islam Pada Produk Deposito Mudharabah di Bank Syariah - Trimulato Trimulato (Iqtishodia: Jurnal Ekonomi Syariah, 2016)
Islamic banking currently has a strong legal law with the presence of the law number 21 of 2008 on Shariah banking. It is very influential on the existence of the Shariah banking are increasingly in demand by many. Islamic bank is better known by the profit-sharing system has a range of products that use Mudarabah and Musharakah contract, considered more equitable for all parties. Bank Indonesia based on the statistics, the number of Mudharabah deposits which have been compiled from third party funds by the banking industry shari'ah until May 2015 was recorded at Rp 129.890 billion rupiah, an increase compared to last year in the same month, deposits from Mudharabah deposits collected amounting to Rp. 119.048 billion rupiah grew 8.35% in the same period last year. Presence of Islamic banks part of Islamic economics, so that every product of Islamic banking is expected in line with the concept of building of Islamic economy. This paper uses a descriptive qualitative limitations in this paper is focused on products in Islamic bank deposits and building concept of Islamic economics. This paper uses literature study from various sources. The results of this paper that the Islamic bank deposit products in line with the concept of building an Islamic economy. Various transactions on deposits has met the economic building islam. Only in certain parts can not be in line with the concept of building an Islamic economy look no aspect of justice. Because they based their refund guarantee on product deposits in Islamic banks.